'Nobody must be allowed to "talk Bible"': Dorothy L. Sayers' Use of the Authorized Version and the Coverdale Psalms in The Man Born to be King. (October 2018) - Wehr, Kathryn
Abstract : Dorothy L. Sayers' 1941–1942 radio play cycle on the life of Christ, The Man Born to be King, is often lauded for its use of the vernacular, though the scholarly discussion of this aspect of her work often creates the false impression that Sayers was working with a Greek New Testament in one hand and a blank piece of paper in the others. This study focuses on the subtle but clear evidence of Sayers' use of the Authorized Version of the Bible, particularly in the areas of narration and Old Testament quotation as well as additional evidence of the Coverdale Psalms from the Book of Common Prayer. Tables at the end of the article also offer the chance for readers to see the evidence upon which conclusions are made and perhaps build for their own research. These three areas—narration, Old Testament quotation and Psalm quotation—, while clearly exceptions to the general rule of original dramatization of biblical material, show Sayers working with all available tools in a dynamic, rather than iconoclastic process.